The opening Dell. (Economist, 2018)
The article discusses the plan of Michael Dell, a billionaire and founder of information technology (IT) company, Dell Technologies, for a public offering to expand its software and cloud offerings. Topics discussed include a brief history of the company, its private offering in 2013 with the help of private-equity firm, Silver Lake Partners, the success of Dell's acquisitions and investments in cloud computing and software and creation of a division focusing on the Internet of Things (IoT).